Pan-immune inflammation value as a prognostic biomarker for cancer patients treated with immune checkpoint inhibitors - Kuang, Tianrui; Qiu, Zhendong; Wang, Kunpeng; Zhang, Lilong; Dong, Keshuai; Wang, Weixing (Frontiers in Immunology, 2024)
Background: Immune checkpoint inhibitors (ICIs) represent a paradigm shift in the development of cancer therapy. However, the improved efficacy of ICIs remains to be further investigated. We conducted a systematic review and meta-analysis to evaluate the pan-immunoinflammatory value (PIV) and PILE score used to predict response to ICI therapy.Methods: We searched selected databases for studies on pan-immune inflammation values and their association with outcomes of treatment with immune checkpoint inhibitors. We used hazard ratios (HRS) and 95% confidence intervals (CI) to summarize survival outcomes. All data analyses were performed using STATA 15.0.Results: 7 studies comprising 982 patients were included in the meta-analysis. The pooled results showed that higher PIV was significantly associated with shorter overall survival OS (HR = 1.895, 95%CI: 1.548-2.318) and progression-free survival (PFS) (HR = 1.582, 95%CI: 1.324-1.890).Subgroup analyses also confirmed the reliability of the results.High PIV and PILE metrics are associated with lower survival in cancer patients receiving ICIs.